The Effectiveness of the Supplementary Feeding Program (PMT) on the Nutritional Status of Children Under Five in the Working Area of Mekar Sari Public Health Center - Kristian Ningtiyas, Linda (Master of Public Health Program Universitas STRADA Indonesia, 2026)
Stunting and malnutrition remain major public health problems in Indonesia. The Supplementary Feeding Program (PMT) is one of the nutritional interventions expected to improve the nutritional status of under-five children.To evaluate the effectiveness of the PMT program on the nutritional status of children under five in the working area of Mekar Sari Public Health Center. A descriptive quantitative study was conducted on 60 under-five children categorized as undernourished or severely undernourished based on WHO growth standards. Body weight data were collected between May and July 2025. Statistical analysis was performed using SPSS to assess changes in average body weight before and after the intervention. The mean initial body weight of the children was 11.0 kg, which increased to 11.4 kg after the PMT intervention, with an average gain of 0.4 kg. A paired t-test showed a statistically significant difference (p = 0.002). The PMT program was effective in improving the body weight of undernourished children. However, the observed increase was modest, highlighting the need for additional interventions such as nutrition education, improved parenting practices, and sanitation improvements.